A new species of Scolecoseps (Reptilia: Scincidae) from coastal north-eastern Mozambique. Issue 1 (2nd January 2018) - Verburgt, Luke; Verburgt, Ursula K.; Branch, William R.
ABSTRACT: Seven specimens of Scolecoseps Loveridge, 1920 from the vicinity of Palma on the north coast of Mozambique are compared morphologically with other known material of this genus . The new material can be distinguished morphologically from all other Scolecoseps by the presence and position of certain head scales, particularly a supraciliary and four small suboculars, a small mental and high subcaudal counts. It is described as a new species, Scolecoseps broadleyi sp. nov . The new species is found in coastal savannah habitat under leaf litter of Berlinia orientalis trees, in sandy soils in close proximity to large wetlands. Its currently known distribution is south of the range of Scolecoseps litipoensis Broadley, 1995 and north of that of Scolecoseps boulengeri Loveridge, 1920. We provide a review of the available literature for the genus Scolecoseps and highlight the necessity for additional research on these poorly known fossorial skinks. ZooBank — Scolecoseps broadleyi : urn:lsid:zoobank.org:act:C4E3723C-F982-4CFA-900B-0B23A9AD5B84